The invisible boy - Ludwig, Trudy (Alfred A. Knopf, 2013)
Meet Brian, the invisible boy. Nobody ever seems to notice him or think to include him in their group, game, or birthday party... until, that is, a new kid comes to class. When Justin, the new boy, arrives, Brian is the first to make him feel welcome. And when Brian and Justin team up to work on a class project together, Brian finds a way to shine.